Odpowiedzi

2009-12-15T16:25:41+01:00
A) 6(5y+1)(1-5y)-(3x+2)(1+4x) = 6(1 + 5y)(1-5y)-(3x + 12x² + 2 + 8x)=
=6(1 - 25y²) - 3x -12x² - 2 - 8x = 6 - 150y² - 11x - 12x² - 2 =
= - 12x² - 150y² - 11x + 4

b) -2(3y+2)(2-3y)-(5x+1)(1-5x)=
= -2(2 + 3y)(2-3y) - (1+5x)(1-5x) =
= -2 (4 - 9y²) - (1 - 25x²) = -8 + 18y² - 1 + 25x² =
= 25x² + 18y² - 9
1 5 1
2009-12-15T16:27:44+01:00
A) 6(5y+1)(1-5y)-(3x+2)(1+4x)
6(1-25y²)-(3x+12x²+2+8x)
-150y²+6-11x-12x²-2=-150y²-12x²-11x+4

b) -2(3y+2)(2-3y)-(5x+1)(1-5x)
-2(4-9y²)-(1-25x²)
-8+18y²-1+25x²=18y²+25x²-9
2009-12-15T16:27:30+01:00
A) 6(5y+1)(1-5y)-(3x+2)(1+4x)= 30y+6(1-5y)-3x-2(1+4x)= 30y+6-30y-3x-2-4x= 4-1x

b) -2(3y+2)(2-3y)-(5x+1)(1-5x)= -6y-8-6y-5x-1+5x= -12y-9